A short chronicle of warfare in South Africa - Information Bureau, Military (Scientia Militaria - South African Journal of Military Studies, 2012)
Khoisan Wars Khoisan is the collective name for the South African people known as Hottentots and Bushmen. It is compounded from the first part of Khoi Khoin (men of men) as the Hottentots called themselves, and San, the names given by the Hottentots to the Bushmen. The Hottentots and Bushmen were the first natives Dutch colonist encountered in South Africa. Both had a relative low cultural development and may therefore be grouped. The Colonists fought two wars against the Hottentots while the struggle against the Bushmen was manned by casual ranks on the colonist farms.